Nutritional Characteristics and Potential Applications of Flour Prepared from Indonesian Wild White Yam (Dioscorea esculenta L.) - Diah Susetyo Retnowati; Ratnawati Ratnawati; Andri Cahyo Kumoro (Dept. of Chemical Engineering, Diponegoro University, 2019)
Gembili or wild white yam (Dioscorea esculenta L.) is one of underutilized tubers that can be found during dry season in Indonesia and other Southeast Asian countries. Although it has been consumed as staple food by people for centuries during famine, no further studies have been conducted to explore its potentials in food applications. This work aims to study the preparation, characterization and potential analysis of Gembili flour for use as raw material in novel foods development. Creamy white flour was obtained from white yam tuber from milling and sieving of dried tuber chips. The flour has water content about 12.08%, which is acceptable for storage. No lipid was detected. In addition, the protein, ash, and fiber content of the flour were respectively 3.00%, 1.27%, and 9.04%. The carbohydrate and amylose contents of the flour were 86.69% and 29.92% indicating its suitability for energy source. As expected, the cyanide content is very low of about 1.688 ppm suggesting that it is safe for consumption. Refer to those properties, Gembili flour can be a promising raw material for the preparation of bakery, cookies, noodle and confectioneries.Keywords: proximate composition, flour, white yam, food, preparation